Financial Ratio Analysis of Gagak Hitam: A Case Study from Indonesia’s Tobacco Industry - Lisabillah , Amiroh (CV. SPDFHarmony, 2025)
Background: The tobacco industry remains one of Indonesia’s key economic sectors but is increasingly threatened by health regulations, rising excise taxes, and shifting public attitudes. Small-scale tobacco companies, such as Gagak Hitam in Bondowoso, face growing financial pressures that require evaluation of their financial resilience. Aims: This study aims to assess the financial performance of Gagak Hitam Cigarette Company from 2014 to 2018 by analyzing key financial ratios—liquidity, solvency, and profitability—to determine the company’s ability to sustain operations amid industry decline and regulatory challenges. Methods: The study uses a descriptive case study approach with purposive sampling, focusing on financial statements and internal management interviews. Financial ratio analysis was applied to audited balance sheets and income statements over a five-year period. Key ratios such as Current Ratio, Quick Ratio, Net Working Capital, Debt Ratio, Debt to Equity Ratio, Gross Profit Margin, Net Profit Margin, and Operating Profit Margin were calculated and interpreted. Findings: The analysis showed a stable financial condition from 2014 to 2017, with strong liquidity and improving profitability. However, in 2018, there was a sharp decline in nearly all indicators, especially profit margins, which dropped significantly. Liquidity weakened, and the company’s reliance on long-term debt increased, raising concerns over financial sustainability. Significance: This study provides empirical insight into the financial vulnerability of regional tobacco firms under regulatory pressure. It highlights the importance of financial ratio analysis as a strategic tool for early risk detection and supports the need for improved financial management and adaptive strategies in small-scale, high-risk industries.